COMPARATIVE ANALYSIS OF «INDIGO» AND «DISPACE 2.0» AUTOMATED TESTING SYSTEMS FOR THE CONTROL OF PERSONNEL KNOWLEDGE - Legan, Marina V.; Afanaseva, Olesya S. (EAI Endorsed Transactions on Energy Web, 2018)
Professional tools for automating the testing and processing of results are now developed. The purpose of research – comparison of capabilities and quality indicators of two automated systems of knowledge control (testing systems) personnel in the Novosibirsk region INDIGO and Dispace 2.0. The study showed a wider and adapted functionality of the LMS DiSpace 2.0 testing module compared to the INDIGO testing system. LMS DiSpace 2.0 can be used not only to control staff knowledge, but also to recommend a platform for training personnel of enterprises.
Keywords: e-learning; blended learning; andragogy; testing system; learning management system